High-speed dynamics and temperature variation during drop impact on a heated surface. (15th June 2022) - Liu, Lihui; Zhang, Yichi; Cai, Guobiao; Tsai, Peichun Amy
Highlights: High-speed impact dynamics and temperature changes are measured experimentally. Theoretical models of drop and surface temperature changes ( Δ T d and Δ T s ) are given. Impact outcomes significantly affect the temperature variations. Δ T d scaling laws are found for non-Leidenfrost drops: Δ T d ∼ t 3 / 2 first and then ∼ t . Negligible temperature changes for Leidenfrost droplets due to a vapor layer. Graphical abstract: Abstract: Drop impact on heated surfaces plays a vital role in numerous applications, such as spraying, cooling, and combustion. In addition to impact dynamics, we investigate both droplet and surface temperature changes using a high-speed infrared (IR) camera and thermocouples when a Milli-Q water droplet impacts on a heated surface under various Weber numbers ( 1.6 ≤ W e ≤ 129, which compares the drop kinetic to surface energy) and initial surface temperature ( 100 ∘ C ≤ T s i ≤ 445 ∘ C ). Theoretical models of droplet and surface temperature changes are deduced using the energy conservation principle. Both theoretical and experimental results show that temperature variations are dramatically influenced by impact dynamics, which shows spreading, spreading/splashing atomization, or complete rebound depending on W e and T s i . For non-Leidenfrost droplets, the experimental results show that the mean droplet temperature change ( Δ T d ) is increased with increasing W e and T s i and scales with Δ T d ∼ t 3 / 2 and Δ T d ∼ t in the initial spreading and later-time sticking stages, respectively. The experimental results of solid surface temperature change, Δ T s c ≡ Δ T s ( z = 0 ), show that Δ T s c alters sharply with W e for W e < 30, whereas insignificantly for W e > 30 with an identical T s i . Under the same W e, Δ T s c increases first for 100 ∘ C ≲ T s i ≲ 300 ∘ C and then reduces when 300 ∘ C ≲ T s i ≲ 445 ∘ C because of enhanced atomization at elevated temperatures. Finally, a negligible Δ T d and a nearly constant Δ T s c ( ≲ 4 ∘ C ) are observed for Leidenfrost droplets due to the formation of an insulating vapor layer formed underneath the bouncing droplet.